A non-matching finite element-scaled boundary finite element coupled method for linear elastic crack propagation modelling. (June 2015) - Yang, Z.J.; Wang, X.F.; Yin, D.S.; Zhang, Ch
Highlights: A novel method coupling SBFE–FE is developed for elastic fracture modelling. The non-matching algorithm makes FE-based remeshing simple but effective. The high accuracy of SIFs is ensured by the semi-analytical SBFE method. The method is validated by modelling a few plane crack propagation problems. Abstract: A novel method coupling the scaled boundary finite element method (SBFEM) and the finite element method (FEM) is developed for linear elastic fracture modelling. A very simple but effective remeshing procedure based on the FE mesh only is used to accommodate crack propagation. The crack-tip region is modelled by an SBFE subdomain whose semi-analytical displacement solutions are used to extract accurate stress intensity factors. The SBFE subdomain is coupled with the surrounding FE mesh through virtual interfaces so that non-matching nodal discretisations of the shared boundaries can be used and only one SBFE subdomain is needed at a crack-tip. A few plane problems are modelled to validate the new method.